Preoperative Patient Education and Smaller Prescription Quantity Reduce Opioid Use After Posterior Spinal Fusion for Adolescent Idiopathic Scoliosis: Results of a Prospective Study. Issue 8 (20th September 2022) - Yang, Daniel; Jha, Sahil; Swallow, Jennylee; Caird, Michelle S.; Lopyan, Alexander; Stepanovich, Matthew; Whyte, Noelle; Li, Ying
Abstract : Background: Most opioids prescribed postoperatively are unused. Leftover opioids are a major source of nonmedical opioid use among adolescents. Postoperative opioid use has also been associated with prescription quantity. Our purpose was to evaluate the effect of preoperative patient education and implementation of evidence-based prescribing guidelines on opioid use and pain level after posterior spinal fusion (PSF) for adolescent idiopathic scoliosis (AIS). Methods: AIS patients aged 10 to 17 years undergoing PSF were prospectively enrolled [postintervention cohort (POST-INT)]. Previous data on 77 patients showed median consumption of 29 doses of oxycodone after PSF [preintervention cohort (PRE-INT)]. All eligible patients during the study period were discharged with 30 doses of oxycodone and standard nonopioid analgesics. Only study participants received education on postoperative pain control. Demographics, radiographic/surgical data, pain level, and patient-reported outcomes were collected. Requests for opioid refills were documented. Results: Forty-nine patients were enrolled. POST-INT was divided into low (L, ≤8 doses), average (AVE, 9-25), and high (H, >25) opioid use groups. Demographics, radiographic/surgical data, pain level, and patient-reported outcomes were similar between the groups. However, there was a difference in days of oxycodone use, doses consumed in the first week, and leftover doses ( P <0.001). Comparison to the PRE-INT L (≤16 doses), AVE (17 to 42), and high (H, >42) use groups showed that POST-INT L and AVE consumed less oxycodone (L: P =0.002; AVE: P <0.001). Also, the overall POST-INT cohort had fewer mean days of oxycodone use (5.6 vs. 8.9, P <0.001) and doses used in the first week (14 vs. 23, P <0.001) compared with the PRE-INT cohort. Subanalysis showed fewer study participants requested and received an opioid refill [3/49 patients (6%)] compared with eligible patients who declined to participate, withdrew, or missed enrollment [8/35 patients (23%)] ( P =0.045). Conclusions: Preoperative patient education and smaller prescription quantity successfully reduced opioid use while maintaining excellent pain control after PSF for AIS. Setting expectations regarding postoperative pain management is critical, as nonstudy participants were significantly more likely to request an opioid refill. Level of Evidence: Level II—therapeutic.